Introducing the Adults with Chronic Healthcare Needs (ACHCN) definition and screening instrument: Rationale, supporting evidence and testing. Issue 2 (April 2018) - Gulley, Stephen P.; Rasch, Elizabeth K.; Altman, Barbara M.; Bethell, Christina D.; Carle, Adam C.; Druss, Benjamin G.; Houtrow, Amy J.; Reichard, Amanda; Chan, Leighton
Abstract: Background: Among working age adults in the United States, there is a large, heterogeneous population that requires ongoing and elevated levels of healthcare and related services. At present, there are conflicting approaches to the definition and measurement of this population in health services research. Objective: An expert panel was convened by the National Institutes of Health with the objective of developing a population-level definition of Adults with Chronic Healthcare Needs (ACHCN). In addition, the panel developed a screening instrument and methods for its use in health surveys to identify and stratify the population consistently. Methods: The panel employed multiple methods over the course of the project, including scoping literature reviews, quantitative analyses from national data sources and cognitive testing. Results: The panel defined the ACHCN population as "Adults (age 18–65) with [1] ongoing physical, cognitive, or mental health conditions or difficulties functioning who [2] need health or related support services of a type or amount beyond that needed by adults of the same sex and similar age." The screener collects information on chronic health conditions, functional difficulties, and elevated use of or unmet need for healthcare services. Conclusions: Adapted from the Maternal and Child Health Bureau definition that identifies Children with Special Healthcare Needs, aligned with the ACS-6 disability measure, and consistent with the HHS Multiple Chronic Condition Framework, this definition and screener provide the research community with a common denominator for the identification of ACHCN.